The Role of Criminal Law as Protection of Human Rights Against Environmental Crimes - Maaliki, Naavi'u Emal (KnE Social Sciences, 2025)
Environmental crimes not only damage ecosystems but also violate human rights (HAM), especially the right to a healthy environment. This article highlights how criminal law can be a tool for protecting human rights in the context of the climate crisis. Using a normative legal approach and case studies, this article discusses the effectiveness of criminal law in protecting the rights of communities, including indigenous peoples and future generations, from the impacts of environmental crimes. It is found that even though environmental criminal law is available, human rights protection through this mechanism is still weak due to an approach that emphasizes ecological losses rather than aspects of individual and collective rights. An approach is needed that places environmental rights as part of fundamental human rights. The policy of formulating criminal law in Indonesia to protect victims of environmental crimes in the future is to improve criminal sanctions and add sanctions such as restitution and compensation as part of the main crime. This is important to provide better protection to victims, especially in cases of environmental crimes by corporations. The addition of restitution and compensation sanctions is also regulated in environmental law, including the mechanisms and amounts of compensation. This concept must be regulated in implementing regulations to avoid uncertainty and harm to victims in implementation in the field.